The G.P.I. and the speech pathologist - Prathibha S Shetty (Journal of All India Institute of Speech and Hearing, 1970)
'Half a century ago general paralysis of the insane constituted a high pro- portion  of  mental  hospital  admissions  and  accounted  for  an  appreciable  part of the chronic population of such institutions.   However, with the development of  increasingly  effective  methods  of treatment,  cerebral  syphillitic  infection is becoming relatively rare' (Mayer-Gross et al., 1960)